Alat Bantu Jalan Penyandang Disabilitas Ganda (DeafBlind) Dengan Peringatan Getaran Berbasis Mikrokontroler - Nizmaldy Astoro Witjati; Ade Zulkarnain Hasibuan; Arnes Sembiring (Unit Pengelola Jurnal Universitas Harapan Medan, 2023)
The sense of sight is a vital source of information that is very important for humans, but not a few people experience problems with their vision. Blindness is a general term used to describe the condition of a person who experiences obstacles or impairments in their visual abilities. Because the function of the sense of vision decreases, blind people maximize the function of other senses such as the sense of touch, smell, hearing, and others. However, there are also blind people who suffer from abnormalities such as the loss of the sense of hearing (deafblind) which is usually called double disability (deafblind). It can be understood that if a person has impaired vision and hearing (deafblind), then their activities are very limited, because the information obtained will be reduced compared to someone with normal vision and hearing. In general, blind people use a cane as a walker to assist movement when walking, therefore, a walker is made that can detect objects or obstacles in front using an ultrasonic sensor based on an arduino nano microcontroller, with vibration output as a warning to people with disabilities. The purpose of this tool is to make it easier for people with multiple disabilities (deafblind) to detect obstacles in front when walking. The results obtained from this tool work accordingly and stably as expected, as evidenced by the detection success rate of 99.26% and a very minimal error rate of 0.74%, and the results of the comfort of using a cane carried out by users (deafblind) reached 70,83% with comfortable criteria.